2021
DOI: 10.1109/tpami.2019.2950923
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Image Degradation and Degradation Removal to CNN-Based Image Classification

Abstract: Just like many other topics in computer vision, image classification has achieved significant progress recently by using deep-learning neural networks, especially the Convolutional Neural Networks (CNN). Most of the existing works are focused on classifying very clear natural images, evidenced by the widely used image databases such as Caltech-256, PASCAL VOCs and ImageNet. However, in many real applications, the acquired images may contain certain degradations that lead to various kinds of blurring, noise, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(83 citation statements)
references
References 84 publications
(73 reference statements)
2
81
0
Order By: Relevance
“…In the BU case, because the gap between the level of training image quality and the level of testing image quality is large, which leads to a low accuracy in classifying the images. The similar results appear in [5]. In the BB case, the accuracy of model aggregation with the CA approach is 2.42% higher than the accuracy of model aggregation with the FedAvg approach.…”
Section: B Accuracy and Efficiency Of Model Aggregationsupporting
confidence: 75%
See 2 more Smart Citations
“…In the BU case, because the gap between the level of training image quality and the level of testing image quality is large, which leads to a low accuracy in classifying the images. The similar results appear in [5]. In the BB case, the accuracy of model aggregation with the CA approach is 2.42% higher than the accuracy of model aggregation with the FedAvg approach.…”
Section: B Accuracy and Efficiency Of Model Aggregationsupporting
confidence: 75%
“…Based on the motion blur level, we try to evaluate the image quality. By [5], we consider that when the motion blur level of training images is more similar to that of testing images, the higher the classifying accuracy is resulted. As a consequence, we measure the image quality by function β that has the form as where L t is the given motion blur level of testing images.…”
Section: A Image Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, although there have been a few investigations on visibility restoration, none have included all essential aspects. Liu et al [4] and Pei et al [5] investigated the effects of image degradation on object recognition. The results demonstrated that the accuracy declined as haze increased.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these problems cannot be alleviated using image processing techniques. In image recognition field, there are various studies about effects of image distortions on the output [16,17,18,19,20,21]. They analyzed the strengths and weaknesses of CNN models against image degradation.…”
Section: Introductionmentioning
confidence: 99%